Displaying Health Status Based IoT - Azizi , Muhammad Arief; Zariman, Asnazulfadhli; Panessai, Ismail Yusuf; Yani, Achmad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Students have many activity in their daily life. There are many things to do like going to class, meeting for group assignment, shopping for food and so on. If the student is unwell then need to go to the clinic for treatment and leaving letter. So in order to reduce the risk of receiving illness, researchers propose Displaying Health Status Based on the Internet of Things Concept. This tool will help students by knowing the pulse rates is normal or not. Displaying Health Status Based on the Internet of Things is designed to facilitate students to see their pulse rate. This tool will also help students to develop their potential and facilitate the health of students themselves by knowing their pulse rate at the proper level. Students will always keep their health healthy for everyday life. Additionally, this tool can alert students that health is essential for life. The results of this research show that this tool can be used when exercising to determine the pulse rate is normal or not.